Halogen- and hydrogen bonding host structures for anion recognition - Bondila, M (2019)
This thesis describes the utilisation of acyclic and interlocked host molecules for anion recognition and sensing in organic media. Halogen bonding is primarily employed as the intermolecular interaction of choice for anion complexation, often assisted by hydrogen bonding. Chapter 1 introduces the field of supramolecular chemistry, with a particular emphasis on supramolecular anion recognition and non-covalent interactions, followed by an overview of mechanically interlocked molecules and their applications. Chapter 2 investigates the construction of amido-(iodo)triazole anion hosts. The synthesis and anion binding properties of a family of cationic and neutral [2]rotaxanes incorporating this motif are reported. In particular, a dramatic increase in iodide affinity upon introducing a halogen bond donor is reported. Chapter 3 explores the preparation and fine-tuning of (thio)urea-(iodo)triazole acyclic receptors, and the resulting anion binding trends are compared and contrasted. Attempts to construct analogous higher order structures are reported. Chapter 4 outlines the exploitation of covalently appended perfluoroaryl motifs for enhancing the anion binding properties of novel carbazole-(iodo)triazole structures. Their anion complexation equilibria are quantified through 1H NMR titration experiments and qualitatively assessed through UV-Vis and fluorescence spectroscopy. Chapter 5 provides a summary of the main conclusions of this thesis. Chapter 6 details the synthetic protocols employed in this work and includes the characterisation of novel and previously reported compounds in Chapters 2 – 4.